Design and Implementation of a Personal Computer Authorization System using Color Detection - Yucel, F.; Oral, O.; Caglayan, N.; Tecimen, M.; Kocak, S.; Yuce, E. (Elektronika ir Elektrotechnika, 2011)
For using of personal computers (PCs) only by authorized persons, there are several methods such as fingerprint or face recognition at logon. In this study, an authorization method based on color detection and coding is designed and implemented. The color on specific coordinate of a color coded card is detected by color sensor with high resolution and converted to RGB code. Then, this code is compared by the RGB codes on a color code database to check the matches. Designed system can also be used cost-efficiently and to be preferable for PCs as in computer laboratories which users are often changed, as PCs in computer laboratories or offices. It also can be adapted to other security systems, and it is low cost. 1ll. 5, bibl. 10, tabl. 1 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.115.9.758